Situação de estudo para ensino de estequiometria : contribuições dessa ferramenta para o processo de ensino e aprendizagem em ciências - Campos, Sarah Gonçalves Alves (2023)
The project aimed to outline new strategies linked to the teaching of Stoichiometry, one of the essential concepts in Science and Chemistry education, through the approach of a Study Situation (SE) entitled "Digital Technologies and Stoichiometry: Navigating Digital Media in Search of the Perfect Mixture." Study situations (SE) represent a variation of thematic approaches, proposing the use of real-life situations from students' everyday lives to explore scientific concepts in a non-linear manner, redefining concepts associated with Science Education. Thus, the overall objective of the research was to construct a Study Situation (SE) that would facilitate the development of Stoichiometry content. The theoretical framework was based on the historical-cultural assumptions of Vygotsky's theory, associated with the epistemological obstacles of Gaston Bachelard. The research was implemented with a 9th-grade class, totaling six pedagogical interventions that addressed digital technologies as the theme of the SE, conducted in the Science discipline at a private school located in the urban area of Bagé-RS city. During the implementation of the activities, questionnaires with open and closed-ended questions were used for data collection, and their responses were investigated through statistical analysis of absolute and relative frequency, as well as discursive textual analysis. The results indicate that the developed SE was beneficial for the construction of students' learning, as it proposed the use of new tools that aided in the development and understanding of Stoichiometry content and related concepts. Therefore, it is concluded that the approach used constructed an SE that can be adopted by other teachers, aiming to provide a new approach to the teaching of Stoichiometry, grounded in a theme so present in students' daily lives, digital technologies.